This question was previously asked in

ESE Electronics 2013 Paper 2: Official Paper

Option 1 : 0

CT 3: Building Materials

2962

10 Questions
20 Marks
12 Mins

F = A + AB̅ + AB̅C

F = A + AB̅(1 + C)

F = A(1 + B̅)

F = A

Hence, the Zero Nand gate is required to implement this function.

Name |
AND Form |
OR Form |

Identity law |
1.A = A |
0 + A = A |

Null Law |
0.A = 0 |
1 + A = 1 |

Idempotent Law |
A.A = A |
A + A = A |

Inverse Law |
AA’ = 0 |
A + A’ = 1 |

Commutative Law |
AB = BA |
A + B = B + A |

Associative Law |
(AB)C |
(A + B) + C = A + (B + C) |

Distributive Law |
A + BC =(A + B)(A + C) |
A(B + C) = AB + AC |

Absorption Law |
A(A + B) = A |
A + AB = A |

De Morgan’s Law |
(AB)’ = A’ + B’ |
(A + B)’ = A’B’ |